Targeted Chinese Medicine Delivery by A New Family of Biodegradable Pseudo-Protein Nanoparticles for Treating Triple-Negative Breast Cancer: In Vitro and In Vivo Study - Kwan, Hiu Yee; Xu, Qinghua; Gong, Ruihong; Bian, Zhaoxiang; Chu, Chih-Chang (Frontiers in Oncology, 2021)
Triple negative breast cancer (TNBC) has the worst overall survival among all breast cancer subtypes; 80% of TNBC harbors TP53 mutation. Gambogic acid (GA) is an herbal compound isolated from the dry brownish gamboge resin of Garcinia hanburyi. A new family of biodegradable polymer, the folate (FA)-conjugated arginine-based poly(ester urea urethane)s nanoparticles (FA-Arg-PEUU NP), was developed as nano-carrier for GA. Its anti-TNBC effects and the underlying mechanism of action were examined. The average diameters of FA-Arg-PEUU NP and GA-loaded FA-Arg-PEUU NP (NP-GA) in water are around 165 and 220nm, respectively. Rhodamine-tagged FA-Arg-PEUU NP shows that the conjugation of FA onto Arg-PEUU NPs facilitates the internalization of FA-Arg-PEUU-NP into TNBC. Compared to free-GA at the same GA concentrations, NP-GA exhibits higher cytotoxicity in both TP53-mutated and non-TP53 expressed TNBC cells by increasing intrinsic and extrinsic apoptosis. In HCC1806-bearing xenograft mouse model, the targeted delivery of GA by the FA-Arg-PEUU-NP nano-carriers to the tumor sites results in a more potent anti-TNBC effect and lower toxicity towards normal tissues and organs when compared to free GA. Furthermore, NP-GA also reduces the tumor-associated macrophage (TAM) M1/M2 ratio, suggesting that the use of Arg-based nanoparticles as carriers for GA not only makes the surface of the nanoparticles positively charged, but also confers on to the nanoparticles an ability to modulate TAM polarization. Our data clearly demonstrate that NP-GA exhibits potent anti-TNBC effects with reduced off-target toxicity, which represents novel alternative targeted therapeutics for TNBC treatment.